Cultura... Culturas: tens??es pentecostais no ensino da religiosidade afro-brasileira - Silva, Jos?? Walter Silva e (2018)
Much has been produced on Law No. 10.639/2003 since its promulgation, especially with regard to the practical aspects of pedagogical practice and its implications for the black movement. Without sacrificing these perspectives, on the contrary, relying on the productions inspired by them, this work entitled "Culture... Cultures: Pentecostal tensions in the teaching of Afro-Brazilian religiosity" deepens such discussions, insofar as it analyzes, as object of study, the influence of the idea of culture of the Pentecostal teachers in the approaches of the teaching of the Afro-Brazilian Culture, with emphasis on the religious manifestations, in the initial series of elementary education of the municipality of S??o Jo??o do Piau??-PI. The construction of the object occurred from the identification of the problematic that suggests a resistance of the professors of Pentecostal faith in relation to teaching of African History and Culture, especially with respect to Afro-Brazilian religious practices, according to the requirements of the norms of the Brazilian Educational System. The evidence of this tension, often silenced in the school universe, led the researcher to formulate the hypothesis that, in the confrontation between the underlying conceptions of culture in the educational guidelines of the Brazilian State and in the practices of Pentecostal teachers, a conflictive movement results, in the limit, failure to comply with norms related to respect for religious diversity between evangelical beliefs and manifestations of the religiosity of Afro-Brazilians. Using a methodology that predicted the use of semi-structured interviews and the application of socioeconomic questionnaires and opinion polls, the research identified that, although Afro-Brazilian religiosity is not treated by the Law No. 10.639/2003, the expected tension ends up to dilute before the practices of negotiation and resignification of the subjects of afroreligious character by Pentecostal morality. It was the categories of Totality and Real Consciousness and Possible Consciousness, of the method of Genetic Structuralism by Lucian Goldmann, that referenced this research.